Taxonomic notes on the Zethus olmecus de Saussure, 1875 species group (Hymenoptera, Vespidae, Eumeninae), with the description of five new species - Lopes, Rogério B. (2024)
Zethus Fabricius is the largest genus within Vespidae with nearly 300 species. The genus has a central role on discussion of social evolution, once some species share behavioral features between solitary and social representatives of vespids and the genus has been recovered as phylogenetically closer to social wasps than to other Eumeninae. The Zethus olmecus species group is even more remarkable since there are observations of communal nesting behavior, a fact misused as support for the hypothesis of closer relationship to social wasps. Herein we closely investigate the taxonomy of this group of species, the first step needed for future studies to properly approach its evolution. The taxonomic approach involved examination of external morphology and male genitalia. Five new species are described for the group: Z. bolivari n. sp., Z. hermesi n. sp., Z. hexacirratus n. sp., Z. perilloi n. sp., and Z. utingensis n. sp. The unknown female of Z. peruvicus is also described. An illustrated taxonomic key is presented. Geographical distribution is expanded for Z. peruvicus, Z. pygmaeus, Z. thoracicus, and Z. toltecus. Finally, additional notes and corrections of existing literature are given.